Research on New SMA Actuator and Bionic Hand - Zhiguang Wu (Jixie chuandong)
A modular underactuated five-finger bionic hand based on polygon SMA actuator is designed. The overall mass is 260 g，each finger can be disassembled and driven independently. The effective length of SMA wire is improved by using the series and put of multi-section steel sheet and SMA wire，and the driving displacement is increased by one time through the inner pulley structure. The mathematical models of driving current and output displacement as well as temperature and driving voltage are established to solve the problems of small driving displacement and poor real-time performance of temperature feedback control. The experimental results show that the new polygon SMA actuator has small volume，light quality，drive a large displacement，through the double feedback current and temperature control algorithm，the precise control of output displacement is realized and the SMA actuator response speed under different environmental temperature is improved，by fetching experiments，the bionic hand grasping ability is verified. The research results provide a way to promote the application of SMA bionic hand.